2006
DOI: 10.1021/jp0555899
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake of Methyl Vinyl Ketone, Methacrolein, and 2-Methyl-3-butene-2-ol onto Sulfuric Acid Solutions

Abstract: To investigate the link between molecular structure, reactivity, and partitioning of oxygenated organic compounds in acidic aerosols, the uptake of three compounds found in the atmosphere, methyl vinyl ketone (MVK), methacrolein (MACR), and 2-methyl-3-butene-2-ol (MBO), by sulfuric acid solutions has been measured using a rotated wetted-wall reactor (RWW) coupled to a chemical ionization mass spectrometer (CIMS). MVK was found to partition reversibly into 20-75 wt % H 2 SO 4 solutions, and we report Henry's la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 46 publications
3
50
0
Order By: Relevance
“…(87) Oligomerization proceeds by the successive addition of a β-hydroxy ketone unit: (88) Yasmeen et al (2010) reported that an aldol condensation type reaction occurs at a higher pH value than acetal formation. Such an aldol condensation reaction has also been found for methyl vinyl ketone (Nozière et al, 2006;.…”
Section: (85)supporting
confidence: 54%
“…(87) Oligomerization proceeds by the successive addition of a β-hydroxy ketone unit: (88) Yasmeen et al (2010) reported that an aldol condensation type reaction occurs at a higher pH value than acetal formation. Such an aldol condensation reaction has also been found for methyl vinyl ketone (Nozière et al, 2006;.…”
Section: (85)supporting
confidence: 54%
“…In order to evaluate the potential importance of carbonyl heterogeneous chemistry and understand the reaction mechanisms of carbonyls in the aerosol phase, a range of carbonyls have been exposed to acidic sulfate either as an acidic film or a pre-existing acidic inorganic seed using either flow reactors (Jang et al, 2003a;Nozière and Riemer, 2003;Zhao et al, 2005Zhao et al, , 2006Nozière et al, 2006) or a Teflon film chamber (Jang and Kamens, 2001;Kroll et al, 2005a). The majority of studies showed that, in general, aldehydes, such as hexanal and octanal, resulted in higher aerosol yields via heterogeneous acid-catalyzed reactions than ketones such as 2-octanone and 2,4-pentanedione .…”
Section: Laboratory Studies Of Aerosol Growth By Acid-catalyzed Reactmentioning
confidence: 99%
“…While aldol condensation products (e.g. from methylglyoxal) are thermodynamically favorable (Barsanti and Pankow, 2005), both experimental and theoretical studies have shown that rate constants of aldol condensation are too low to be important for significant aqSOA formation under typical atmospheric conditions (0.074 M −1 s −1 < k aldol < 15 M −1 s −1 (Casale et al, 2007;Minerath and Elrod, 2009) Noziere et al, 2006).…”
Section: Dark Reactions Of Carbonyl Compoundsmentioning
confidence: 99%